TELAAH VARIASI BAHASA DALAM INTERAKSI JUAL BELI DI PASAR PAGI LEMABANG - Adelia Ningsi; Ayu Puspita Indah Sari (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This study aims to analyze the study of language variations used in buying and selling interactions at Lemabang Morning Market. The research method used is a qualitative approach with data collection techniques through observation and interviews. The collected data were analyzed using descriptive analysis to identify language variations in buying and selling interactions. The results showed that there were significant language variations in buying and selling interactions at the Lemabang Morning Market. The most dominant language variations are language variations in terms of speakers. This discovery provides insight into the complexity of language in the context of traditional markets and can form the basis for efforts to preserve and develop language in this community.